Development of a method to classify and analyse the composition of mixed waste materials in real-time. - Vrancken, Carlos (Cranfield University, 2022)
There is a need for innovative technologies to classify and monitor the composition of solid waste in real-time. This research project has highlighted which information is required to improve current process designs. It also identified visible spectrum cameras as the solution that can better inform waste composition and quality without requiring complementing technologies. The experiments applied deep learning methods to classify the materials based on their images, and a method to analyse the composition of mixed waste was developed. There is a high variability in the appearance of waste materials in the context of a material recovery facility. An image capture setup using multiple cameras and light sources was implemented and tested to acquire a representative set of images. The hardware captures images from different angles, with enhanced shadow details, and different exposure levels. Image processing software further augmented the data by rotating and changing the images resolutions. The images were converted to greyscale to increase the method robustness without affecting classification performance. Deep convolutional neural networks were trained on the augmented datasets. The trained networks obtained state-of-the-art performance when tested and validated for the task of waste material classification. Based on this, a composition analysis methodology was developed and tested with mixed material samples. The methodology provides results as accurate as current manual solutions, but it can analyse a waste stream on a conveyor belt in real-time. The findings and observations from the experimental results contribute to knowledge in three main areas: data capture, data processing, and deep learning. This thesis presents the progressive development of the methodology and discusses different applications for waste management. The composition analysis can provide real-time waste data to improve the overall efficiency of the waste treatment industry. This information can be also used by stakeholders for better decision-making in the future.
Philip Longhurst - Associate Supervisor
Keywords: Visible spectrum camera; waste composition; waste quality; image processing; deep convolutional neural networks; waste treatment